Targeting the gut microbiota to enhance the antitumor efficacy and attenuate the toxicity of CAR-T cell therapy: a new hope? - Zhang, Peng-Fei; Xie, Dan (Frontiers in Immunology, 2024)
Chimeric antigen receptor (CAR) -T cell therapy has achieved tremendous efficacy in the treatment of hematologic malignancies and represents a promising treatment regimen for cancer. Despite the striking response in patients with hematologic malignancies, most patients with solid tumors treated with CAR-T cells have a low response rate and experience major adverse effects, which indicates the need for biomarkers that can predict and improve clinical outcomes with future CAR-T cell treatments.Recently, the role of the gut microbiota in cancer therapy has been established, and growing evidence has suggested that gut microbiota signatures may be harnessed to personally predict therapeutic response or adverse effects in optimizing CAR-T cell therapy. In this review, we discuss current understanding of CAR-T cell therapy and the gut microbiota, and the interplay between the gut microbiota and CAR-T cell therapy. Above all, we highlight potential strategies and challenges in harnessing the gut microbiota as a predictor and modifier of CAR-T cell therapy efficacy while attenuating toxicity.